Patrimoine et territoire, les nouvelles ressources du développement - Pierre-Antoine Landel; Nicolas Senil (Développement Durable et Territoires)
The initiative proposed here joins in the theoretical frame at present worked around the notion of territorial resource. It proposes a second reading of the various works engaged on this notion, tries to bring it some additional elements and confronts these theoretical propositions with a first analysis of the files deposited by the 342 territories having answered the call to project "Pôles d'excellence rurale" launched by the Interministerial Delegation for Territorial Planning and Competitiveness (DIACT) in December, 2005. The analysis of the projects of development, allows in the end to propose an interpretation ofthe notion of sustainable development. Rather than to constitute an autonomous notion, it would be in fact about an intermediate between a productivist mode of development and a mode of development which we consider as patrimonial.